Genetic Information, the Principle of Rescue, and Special Obligations - Liao, S. Matthew (The Hastings Center report, 2018)
In “Genetic Privacy, Disease Prevention, and the Principle of Rescue,” Madison Kilbride argues that patients have a duty to warn biological family members about clinically actionable adverse genetic findings. The duty does not stem from the special obligations that we may have to family members, she argues, but rather follows from the principle of rescue, which she understands as the idea that one ought to prevent, reduce, or mitigate the risk of harm to another person when the expected harm is serious and the cost or risk to oneself is sufficiently moderate. We doubt, however, whether the principle of rescue can ground a duty to warn in the cases Kilbride envisages, and we suggest that Kilbride may have underappreciated the role that special obligations could play in generating a duty to warn family members.